Management of Coastal Areas with Sustainable Marine Ecotourism Development in Purworejo Regency, Central Java, Indonesia - Hidajat, Wahju Krisna; Anggoro, Sutrisno; Najib, Najib (Universitas PGRI Semarang, 2020)
The beach is a favorite tourist destination for the Indonesian people. As Indonesia is blessed with many beaches which attracts people to visit. Indonesians usually come to the beach in the holiday to fish, see beautiful scenery, and play around. Central Java Province in Indonesia has a beach cluster situated to the north and south of the Java Island. Jatimalang Beach is the south coast of Java which has excellent natural beauty, which is located in Purworejo Regency. This research is focused on the beach facilities and infrastructures, tourist’s ecotourism awareness, and environmental sustainability management of the Jatimalang Beach Purworejo. The study was carried out in November till December 2019 by using the qualitative research method. Information discovered during fieldwork are used to direct data collection. Qualitative researchers, are closely engaging with the environment being examined. This work was conducted through observations and interviews with tourist at Jatimalang Beach, as well as a literature review. The results showed that the facilities and infrastructure found in Jatimalang Beach were the presence of lifesavers, waste, parking lots, freshwater swimming pools for children, toilets, electrical facilities, and worship places. In addition, tourists are often willing to preserve nature and the sustainability of marine tourism on the Jatimalang Beach, however many of them do not understand the importance of ecotourism and need to be educated again.